REFLEKSI PEMIKIRAN TAHIR HADDAD DAN PANGARUHNYA PADA STATUS WANITA DAN PEMBARUAN HUKUM KELUARGA DI TUNISIA - Munawaroh, Lathifah (Moderation | Journal of Islamic Studies Review, 2022)
Family law reform in Tunisia cannot be separated from the thoughts of a feminist named Tahir Haddad. He wrote a book entitled Imra'tuna fi al-sharia wal-mujtama which became the forerunner of family law reform in Tunisian legislation. This book stems from her anxiety to see the situation and social conditions experienced by Tunisian women. Even though this book received extraordinary challenges from Tunisian religionists, Haddad continued to fight for it, until this book had an effect on the reform of family law in Tunisia and also affected the status of women there. This research is a library research with documentation method. This study finds that family law reform in Tunisia in many points uses the extradoctrinal reform method. This method, in principle, no longer refers to conventional fiqh concepts, but refers to the texts of the Qur'an and the sunnah of the Prophet Muhammad, by conducting ijtihad by reinterpreting the texts (reinterpretation) or by using siyasa syar'iyyah based on benefit. With the renewal of family law in Tunisia, the status of women has been elevated, and even almost equal to that of men, except only in the issue of inheritance, which is still a “black hole” in Tunisian history.